Conventional Near-Infrared Spectroscopy and Hyperspectral Imaging: Similarities, Differences, Advantages, and Limitations - Daniel Cozzolino (Molecules, 2025)
Although, the use of sensors is increasing in a wide range of fields with great success (e.g., food, environment, pharma, etc.), their uptake is slow and lower than other innovations. While the uptake is low, some users, producers, and service industries are continuing to benefit from the incorporation of technology in their business. Among these technologies, vibrational spectroscopy has demonstrated its benefits and versatility in a wide range of applications. Both conventional near-infrared (NIR) spectroscopy and hyperspectral imaging (HSI) systems are two of the main techniques utilized in a wide range of applications in different fields. These techniques use the NIR region of the electromagnetic spectrum (750–2500 nm). Specifically, NIR-HSI systems provide spatial information and spectral data, while conventional NIR spectroscopy provides spectral information from a single point. Even though there is a clear distinction between both techniques in terms of their benefits, confusion still exists among users about their similarities and differences. This paper provides a critical discussion of the main advantages and limitations of both techniques, focusing on food science applications.